الكليات الجامعة الاهلية في العراق: تجارب ونظرة تقويمية - مسارع الراوي (PROSPECTIVE RESEARCHES, 2023)
This study focuses on three pivotals. The first one deals with the historical background of education in Iraq. The second concentrates on the higher education and it's objectives. The third pivotal focuses on Al-Mustanssria experiments in this field. The present study suggests two propositions for the staff in charge of higher education and for the postgraduate students Make a suggestive study for establishing a private official university expecting to have a better efficiency for the working class and as a motivation for future official growth. An attempt to be made in order to reform the private university colleges in Iraq, according to certain scientific and objective measures.